The Sirens of Baghdad : A Novel - Yasmina Khadra; Translated from the French by Cullen, John, 1942- (New York Anchor Books, 2008)
"A young Iraqi student, unable to attend college because of the war, sees American soldiers leave a trail of humiliation and grief in his small village. Bent on revenge, he flees to the chaotic streets of Baghdad where insurgents soon realize they can make use of his anger. Eventually he is groomed for a secret terrorist mission meant to dwarf the attacks of September 11, only to find himself struggling with moral qualms"-
Keywords: Iraq--Baghdad -- Radicalism -- Revenge